2007
DOI: 10.1146/annurev.cellbio.23.090506.123529
|View full text |Cite
|
Sign up to set email alerts
|

SNARE-Ware: The Role of SNARE-Domain Proteins in Plant Biology

Abstract: In yeast and animal cells, members of the superfamily of Nethylmaleimide-sensitive factor adaptor protein receptor (SNARE)-domain-containing proteins are key players in vesicle-associated membrane fusion events during transport processes between individual compartments of the endomembrane system, including exocytosis and endocytosis. Compared with genomes of other eukaryotes, genomes of monocotyledonous and dicotyledonous plants encode a surprisingly high number of SNARE proteins, suggesting vital roles for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
295
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(310 citation statements)
references
References 130 publications
(139 reference statements)
4
295
0
2
Order By: Relevance
“…The Arabidopsis Qa-SNAREs SYP121 (=SYR1/PEN1) and SYP122 exhibit high sequence homology and overlapping functions, and both are present at the plasma membrane of cells throughout the plant (Lipka et al, 2007;Bassham and Blatt, 2008). Along with the Qa-SNARE SYP132, which is constitutively expressed and present at low levels (Enami et al, 2009), these proteins mediate secretory vesicle traffic, contributing to cellular homeostasis, expansion, and growth (Blatt, 2000;Shope et al, 2003;Campanoni and Blatt, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arabidopsis Qa-SNAREs SYP121 (=SYR1/PEN1) and SYP122 exhibit high sequence homology and overlapping functions, and both are present at the plasma membrane of cells throughout the plant (Lipka et al, 2007;Bassham and Blatt, 2008). Along with the Qa-SNARE SYP132, which is constitutively expressed and present at low levels (Enami et al, 2009), these proteins mediate secretory vesicle traffic, contributing to cellular homeostasis, expansion, and growth (Blatt, 2000;Shope et al, 2003;Campanoni and Blatt, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SNAREs drive the fusion of vesicle and target membranes and enable the transfer of soluble and membrane-associated cargos in a highly regulated manner (Pratelli et al, 2004;Jahn and Scheller, 2006;Lipka et al, 2007;Bassham and Blatt, 2008). In plant cells, SNARE-mediated vesicle traffic delivers wall materials and membrane to the cell surface, making essential contributions to homeostasis, cell expansion, and growth (Blatt, 2000;Shope et al, 2003;Campanoni and Blatt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Vesicle fusion is accomplished through the action of SNARE proteins (for review, see Lipka et al, 2007), tethering factors (Rab GTPases; for review, see Zerial and McBride, 2001;Molendijk et al, 2004), and presumably aided by components of the exocyst complex (Segui-Simarro et al, 2004), although, to date, mutants defective in subunits of this complex have only been implicated in polar growth (Cole et al, 2005;Wen et al, 2005;Synek et al, 2006;Lavy et al, 2007). The darkstained vesicles were also found in the vicinity of the Golgi apparatus, and it was concluded that they were Golgi derived.…”
Section: Origin Of Cell Plate-building Vesiclesmentioning
confidence: 99%
“…It is generally accepted that members of the soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) superfamily are key factors to drive vesicle fusion events in eukaryotes including yeasts, animals and plants (Jahn and Scheller, 2006). Plant genomes contain a larger number of SNARE genes than yeast and animals, implying a higher degree of sub-functionalization as illustrated by the engagement of distinct SNARE genes in different biological processes such as cytokinesis, gravitropism and disease resistance (Lipka et al, 2007;Sanderfoot, 2007).…”
Section: Introductionmentioning
confidence: 99%